Becoming and being a teacher: the challenges of teaching - Mendes, Thamiris Christine; Baccon, Ana Lúcia Pereira (Revista Hipótese, 2015)
The article turns to the interfaces between becoming a teacher and the challenges of teaching. Data were collected through semi-structured interviews with eight teachers from Paraná state. The results showed that becoming a teacher, to those surveyed, it was a process influenced by family members and by the choice of higher education more accessible for them. The challenges of being a teacher refer to the complexity of interpersonal relationships that permeates the profession.
Keywords: Teaching profession; Teacher training; Teaching